Domestic Investment and the Cost of Capital in the Caribbean - Roache, Shaun (Washington, D.C. : International Monetary Fund, 2006)
Investment-to-GDP ratios across the Caribbean tend to be relatively high. In many countries, these ratios have been trending higher since the mid-1990s, largely reflecting public investment and foreign direct investment. Private domestic investors have been less prominent. This may be one reason why such high investment has delivered Caribbean growth rates below the middle-income average. This paper seeks to understand how higher private investment may be encouraged. Using new data, it concludes that: the multiplier effects of public investment and FDI on private domestic investment are weak; and private domestic investment (PDI) is sensitive to the cost of capital. Public policy designed to raise PDI should focus on creating conditions for a lower cost of capital. The focus should be on removing barriers to lower real interest rates, rather than the further extension of costly tax concessions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet